Um estudo teórico e experimental de nanoestruturas de 'ZnS': propriedades físicas e químicas - La Porta, Felipe de Almeida [UNESP] (2014)
In the last decades the structural and electronic order-disorder effects in semiconductor materials have been one of the most active areas of research in nanoscience. In particular, these effects influence the physical and chemical properties of semiconductor materials and open a new field of study for applications in nanotechnology. In this context, the aim of this work is mainly focusing on the study of the effects of order-disorder structural and electronic, favoring the process of charge transfer in different multifunctional nanostructures based on zinc sulfide (ZnS), such as pure ZnS, M-doped ZnS (M = Mn+2 or Pr+3) and ZnS:M@ZnS heterostructures obtained by microwave-assisted solvothermal method. Different synthetic strategies have been investigated in this work, which enabled a sensitive adjustment of its physical and chemical characteristics of these new nanostructures based on ZnS. The origins of photocatalytic and photoluminescent properties of these nanostructures of ZnS, as well as the mechanisms involved during the phase transition induced by pressure of the three phases of ZnS (cubic zinc blende (ZB), wurtzite hexagonal (W), cubic rock salt (RS)), using various theoretical and experimental methodologies (such as XRD, XPS, FE-SEM, TEM, UV - vis, PL) in order to better understand their properties at a more fundamental level. A deep analysis of the band structures and density of states provide a deep insight into the main characteristics based on the structural and electronic effects order-disorder in the tetrahedral clusters of ZnS. These studies have a fundamental aspect, especially aiding in the development of new materials and devices with highly adjustable properties. All our findings show a good agreement between theoretical and experimental results and lead to new perspectives and ideas on streamlining the properties of these nanomaterials of an atomic level.